TINJAUAN HUKUM LAUT INTERNASIONAL TERHADAP PENELITIAN ILMIAH KELAUTAN TANPA IZIN OLEH KAPAL RISET TIONGKOK DI ZONA EKONOMI EKSKLUSIF INDONESIA - NIM. A1011201176, YUDHA ELSA SATRIA (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstract The purposes of this research are to analyze the legal review of unauthorized marine scientific research activities conducted by the Chinese research vessels Nan Feng and Hai Yang Di Zhi 10 in the Indonesian Exclusive Economic Zone based on 1982 Convention on the Law of the Sea and Indonesian national laws and to analyze the actions that Indonesia can take against the unauthorized marine scientific research in the Indonesian Exclusive Economic Zone and to resolve problems in the North Natuna Sea.The research method used by the author is normative juridical research, because the research is referring to the applicable regulations that is related to topics of the research. The type of data used in this research is secondary data that are related to the subject of the research. The data collection method used is library research using qualitative data analysis method with a prescriptive approach in order to get suggestions on what to do to solve the related problems.Based on the analysis of international maritime laws in the UNCLOS and Indonesian national laws, none of it can justify the unauthorized marine scientific research activities by Chinese research vessels. Therefore, China has violated the applicable regulations in the UNCLOS and Indonesian national laws. China also has violated Indonesia